The social development and the care of the Pachamama in the rural parish of San José. Pastaza - Ecuador - Auquilla Belema, Luis Armijo (2016)
The research was conducted in the rural parish of St. Joseph who belongs to the canton Santa Clara and the province of Pastaza, and its main purpose is to identify the economic activities carried out in this territory; for this, participatory workshops were held with leaders who are directly involved in the administration of 25 community enterprises that are running (president, secretary and treasurer). As a result of these workshops a survey, the same that was validated by a pilot test was developed. From this the definitive survey, which was applied to 75 managers, was developed. The results show that the main economic activity carried out in this area is agriculture, which accounts for 66.94%. This activity is closely related to the Pachamama is done in the traditional manner (without chemical fertilizers) without taking into account that soils are poor and therefore soluble chemical fertilizers needed to feed the plants. The seeds themselves in the area are of low quality, produce little or crops are not good, at which the use of improved seeds promotes increased production. This problem has allowed local farmers to expand the agricultural frontier indiscriminately. It is concluded that working the land by using organic technologies.